Effect of rare earth yttrium and the deformation process on the thermal deformation behavior and microstructure of pure titanium for cathode rolls - Zhenguo Hou; Haitao Liu; Longlong Lu; Weiqiang Li; Zihao Zhang; Weiwei Lu; Qing Feng; Bo Jia; Kexing Song (Journal of Materials Research and Technology)
This study explores the challenges associated with microstructural refinement and homogenization control for large titanium cathode rolls utilized in electrolytic copper foil production. An innovative deformation control strategy was developed by incorporating yttrium microalloying within the β→α dual-phase region to refine the hot-deformed microstructure of pure titanium. Gleeble thermal simulation tests were performed to assess the impact of rare earth Y, deformation temperatures (700–900 °C), and interpass cooling rates (5 °C/s, 25 °C/s, and 50 °C/s) on the hot deformation behavior and microstructural evolution of pure titanium. The results reveal that Y2O3 particles generated by the addition of rare earth Y enhance dynamic recrystallization through the particle-stimulated nucleation (PSN) mechanism, effectively pinning grain boundaries and impeding recrystallized grain growth. Increased interpass cooling rates lead to finer grains and higher stored energy. The mechanism for grain refinement during dual-phase deformation is described as follows: β-phase nonrecrystallization temperature deformation → rapid cooling control → α-phase recrystallization deformation control, energy storage, strain-induced dynamic phase transformation (SIDT, α→β), and dynamic recrystallization (DRX). Under experimental conditions of β-phase region deformation at 980 °C → inter-pass cooling rate of 50 °C/s → α-phase region deformation at 750 °C, the addition of rare earth yttrium achieved the most effective grain refinement, reducing the average grain size to 2.56 μm.